Through the dark continent: African trypanosome development in the tsetse fly - ROTUREAU, Brice; VAN DEN ABBEELE, Jan (Frontiers in Cellular and Infection Microbiology, 2013)
African trypanosomes are unicellular flagellated parasites causing trypanosomiases in Africa, a group of severe diseases also known as sleeping sickness in human and nagana in cattle. These parasites are almost exclusively transmitted by the bite of the tsetse fly. In this review, we describe and compare the three development programs of the main trypanosome species impacting human and animal health, with focus on the most recent observations. From here, some reflections on research issues on the trypanosome developmental biology in the tsetse fly to be addressed in the future are given.